Study of trust‐based mechanism and its component model in MANET: Current research state, issues, and future recommendation. (6th June 2019) - Khanna, Nitin; Sachdeva, Monika
Summary: Security against routing attacks in MANET is most critical issue and traditional concepts of cryptography, authentication, or Watchdog are not that significant in mitigation of these attacks. In recent years, trust‐based approach provides a reputation system that compose of different components to provide security against routing attacks. In this paper, we provide an in‐depth analysis of various components that are used in trust‐based mechanism and techniques deployed in effective and efficient execution of task by the components. Trust‐based mechanisms generally have five components: monitoring and information gathering, trust calculation and evaluation unit, trust recommendation unit, decision‐making and dissemination of detection unit. All or some of these units cooperate together to provide a reliable communication environment with the aim to prevent routing attacks from participating in route formation process and detect attacking nodes simultaneously. Different routing attacks and measures in trust‐based mechanism along with some published work are discussed to understand the implementation of this type of mechanism. Various related issues are explored, discussed, and recommendations are pointed out for future research work in this field. Abstract : In this paper, we provide an in‐depth analysis of component model of trust‐based mechanism and techniques deployed in effective and efficient execution of task by the components. Different routing attacks and measures in trust‐based mechanism along with some published work are discussed to understand the implementation of this type of mechanism. Various related issues are explored, and recommendations are pointed out for future research work in this field.